The Relationship between Hemoglobin Levels and Erythrocyte Morphology on the Third Day of Menstruation for Students in The Faculty of Health - Azzaubadilluah Azzaubadilluah; Andreas PutroRagil Santoso (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2022)
Menstruation is the process of releasing the endometrial lining of the uterus due to the release of the hormones estrogen and progesterone, causing bleeding after ovulation from the uterus for approximately fourteen days at regular intervals. The first three days of menstruation is a condition where there is heavy bleeding, so there is iron loss, which can cause a decrease in hemoglobin levels and there is a risk of causing anemia. The occurrence of anemia gives an illustration of morphological changes of erythrocytes. The objective of this study was to determine the relationship between hemoglobin levels and erythrocyte morphology on the third day of menstruation. This type of research is analytic observational with a cross-sectional approach. The sample in this study were 30 students from the Health Faculty of Nahdlatul Ulama University Surabaya who experienced menstruation on the third day. The hemoglobin level was analysed using the Hematology Analyzer Xp-300 method. A blood smear test with Giemsa stain were used for abnormalities erythrocytes morphology observation. The results of the statistical analysis used the chi-square test showed there was no relationship between hemoglobin levels and erythrocyte size (p-value = 0.836), erythrocyte shape (p-value = 0.416). However, there was a relationship between hemoglobin levels and erythrocyte colour (p<0.05). Based on the study result, it can be concluded that there is no relationship between hemoglobin levels and erythrocyte morphology on the third day of menstruation.